The study of reproductive system G.pusilla by method of detection of genetic diversity (Experimental biology, 2015)
Gagea pusilla is spring geophyt, characterized by mixed reproductive strategies. They relies on vegetative reproductionby subterranean bulbils in young stages but completely switches to sexual reproduction once a certain bulb size is attained.In this study AFLP-genotyping method was used to investigate the consequences of these reproductive strategies forgenetic diversity. In most cases G. pusilla has generative reproduction and it is reflected by the comparatively highgenotypic richness within populations and the low numbers of samples per clone.
Keywords: AFLP fingerprinting; G. pusilla; genetic diversity; reproductive system